The Effect Of Variations In Carbopol Concentration On The Physical Characteristics And SPF Value Of Sunscreen Spray Gel With Ethanol Extract Of Kepok Banana Flowers (Musa Acuminata X M. Balbisiana) By UV-Vis Spectrophotometry - Nikita Puspa; Rahmat Hidayat; Alfina Nurrahman (CV. AFDIFAL MAJU BERKAH, 2026)
Excessive exposure to UV rays can cause various skin damage so that sunscreen preparations are needed. Kepok banana flowers (Musa acuminata x M. balbisiana) contain flavonoid compounds that have the potential as active ingredients in natural sunscreens, especially in the form of spray gel preparations. This study aims to determine the effect of variations in carbopol concentration on the physical characteristics and SPF value of spray gel preparations using UV-Vis spectrophotometry, and to determine the most optimal formula. Ethanol extract of kepok banana flowers was obtained by maceration method using 96% ethanol. Sunscreen spray gel from ethanol extract of kepok banana flowers was formulated with variations in carbopol concentrations of 0,5% (F1), 0,75% (F2), and 1% (F3). The resulting spray gel was tested including organoleptic, homogeneity, pH, viscosity, adhesion, spray pattern, and SPF value. The results showed that variations in carbopol concentration significantly affected the physical characteristics of the preparation, especially the organoleptic texture, pH, viscosity, and spray pattern, but did not significantly affect the SPF value of the spray gel preparation of ethanol extract of kepok banana flowers (Musa acuminata x M. balbisiana). Formula 2 with a carbopol concentration of 0,75% was determined as the most optimal formula with the most balanced physical characteristics and an SPF value of 15.616 with an ultra protection category.